Genetic diversity and heritability estimate of Jatropha curcas L. accessions using agro-morphological and molecular markers - Arolu, Ibrahim Wasiu (2012)
Genetic diversity analysis is the measure of genetic relationship among individual germplasm existing in a population. This research work aims at studying the genetic diversity, heritability pattern and genetic advances in Jatropha curcas germplasm and finally to identify promising groups of accessions that will be used as parent in the future breeding and improvement program. Forty-eight accessions of Jatropha curcas collected from the state of Kelantan, Selangor and Terengganu were planted using randomized complete block design (RCBD). Eleven agro-morphological traits including seed yield/ha were evaluated. Heritability values, principal component analysis were calculated. Cluster analysis was carried out to determine the diversity of Jatropha curcas. Ten ISSR primers were also used to determine molecular diversity in the three populations. In this study, all the morphological traits showed wide variability with highly significant differences among the 48 accessions except for seed width. Positive and significant correlation coefficients were observed among collar diameter, number of secondary branches and number of primary branches. Positive relationship was also observed among seed yield/ha, oil yield/ha and total number of seeds. High broad sense heritability was observed for all traits except for seed width and number of primary branch. The highest heritability was recorded for collar diameter (89.40%), while the least value for this parameter was seed width (-0.02%). Cluster analysis using agromorphological markers and ISSR markers partitions the 48 accessions into 11 and distinct groups at coefficient of 1.1 and 0.6 respectively. From this molecular study, the 48 accessions were clustered into 11 groups at a coefficient of 0.65 without any regard for their geographical origin. The clusters were also formed at medium range coefficient. The mean values of number of alleles, number of effective alleles,shannon’s information index, expected heterozygocity and percentage polymorphic loci are 1.93, 1.69, 0.56, 0.38 and 96% respectively. The percentage variation within and among the populations as shown by analysis of molecular variance are 94% and 6% respectively The principal component analysis revealed that about 75% of total variation as a result of the first three components with PC1, PC2 and PC3 having 61.69, 8.68 and 5.07%, respectively. The three dimensional principal component analysis does not show any distinct relationship among these accessions at a very low coefficient. From the analysis of genetic diversity pattern and estimation of heritability,it can be concluded that collar diameter, number of primary branches, seed yield/accession are useful traits upon which selection can be made. Therefore, accession from cluster II (Accessions B-01-04 and T-01-09) and cluster X (Accessions D-02-02) recommended as parent groups for future breeding programmes.